Adolescent personality development as a longitudinal marker for burnout and happiness in emerging adulthood. (May 2023) - Arslan, İldeniz B.; Lucassen, Nicole; de Haan, Amaranta D.; Jongerling, Joran; Bakker, Arnold B.; Prinzie, Peter
This study examined whether individual differences in personality (development) from adolescence to emerging adulthood were associated with burnout and happiness in emerging adulthood. At Time 1 (2009; M age  = 15.7 years), Time 2 (2012), and Time 3 (2015), Belgian participants ( N  = 329; 43.1% boys) reported on the personality dimensions of extraversion, agreeableness/benevolence, conscientiousness, emotional stability, and openness/imagination. Burnout (exhaustion, disengagement) and happiness (life satisfaction, overall affect) were measured through self-reports at Time 4 (2018). For each personality dimension, except benevolence, higher levels were associated with fewer burnout symptoms. Initial levels of all personality dimensions were related to more happiness. Shallower decreases in extraversion, emotional stability, and stronger increases in imagination were related to fewer burnout symptoms and more happiness. Results indicate the importance of studying personality development as a determinant of later well-being, above and beyond effects of initial levels. Findings offer new insights into the field of personality, occupational, and positive psychology.